Electromagnetic Wave Theory and Applications - Kong, Jin Au; Ding, Kung Hao; Shin, Robert T.; Yang, Ying-Ching Eric; Scire-Scappuzzo, Francesca; Tsang, Leung; Souyris, Jean-Claude; Atkins, Robert G.; Au, William W.; Ewe, Hong-Tat; Hsu, Chih-Chien; Johnson, Joel T.; et al. (Research Laboratory of Electronics (RLE) at the Massachusetts Institute of Technology (MIT), 1994)
Contains table of contents for Section 3, reports on three research projects and a list of publications. California Institute of Technology/Jet Propulsion Laboratory Contract 959548 National Aeronautics and Space Administration Grant NAGW-1617 National Aeronautics and Space Administration Grant Contract 958461 U.S. Navy - Office of Naval Research Grant N00014-92-J-1616 U.S. Navy - Office of Naval Research Grant N00014-92-J-4098 Digital Equipment Corporation AGMT DTD 11/16/93 Joint Services Electronics Program Contract DAAL03-92-C-0001 Joint Services Electronics Program Grant DAAH04-95-1-0038 MIT Lincoln Laboratory P.O. No. BX-5424 U.S. Navy - Office of Naval Research Grant N00014-90-J-1002 U.S. Navy - Office of Naval Research Grant N00014-89-J-1019 DEMACO Agreement 11/15/93 Federal Aviation Administration Grant 94-G-007 U.S. Army Cold Regions Research and Engineering Laboratory Contract DACA89-93-K-0009